Dividing the mind: the necessary role of the frontal lobes in separating memory from search. - Soto, D; Humphreys, G; Heinke, D (2006)
Working memory plays a crucial role in the control of visual selection. Previous research has shown that attentional deployment can be biased to objects in an array matching the contents of working memory. Here, we examined the role of the frontal cortex in determining the interaction between working memory and attention. At the start of each trial, participants memorized an object cue that could contain either the target or a distracter, when the object reappeared in the subsequent search array. Relative to age-matched controls, patients suffering from damage to the frontal lobes showed a stronger effect of the memory stimulus on search. Interestingly, there was an effect of frontal damage on the mean latencies to fixate targets but the effect of memory validity on the number of first saccades to the target, and their time of initiation, was similar across the groups. The results suggest that, following the earliest deployment of attention, frontal lobe structures are involved in separating relevant target from irrelevant (object cue) information, when both are held in memory.